The Use of Learning Management Systems in the Educational Process: The Expediency and Benefits - Shumeiko Nataliа (Educological discourse, 2024)
The article is dedicated to analyzing the ways that help the pedagogue organize the educational process using modern technologies. Technology has been developing rapidly and constantly. Therefore, pedagogues use modern-day technological achievements, particularly the learning management systems (LMSs) at higher education institutions. This study aims to provide information regarding the learning management systems, defining essential principles of their use at the university level and outlining the apparent benefits. The research considers the expediency of using LMSs in the educational process. The author notes the proliferation of open-source software (OSS) within the sphere of education. The reasons for the spread and acceptance of OSS in higher education institutions are delineated. The paper describes Moodle, Claroline, and ILIAS as learning management systems that help effectively organize the learning process online or in a blended learning format. The conclusions support the idea that the learning management systems, being at the forefront of the latest technological advancements, satisfy the requirements of pedagogues and students within the interaction in a virtual learning environment.